CINTA KASIH YUDISTIRA DALAM KOMUNIKASI ANTARPRIBADI ANTARA YUDISTIRA DENGAN DEWA INDRA DALAM CERITA MAHABHARATA - I NYOMAN ALIT SUARJAYA (GANEC SWARA, 2022)
This research is entitled "Yudistira's Love in Interpersonal Communication between Yudistira and Dewa Indra in the Mahabharata Story". Raising two problem formulations, namely how is interpersonal communication in the conversation between Yudistira and Dewa Indra? And how is Yudistira's love in interpersonal communication between Yudistira and Dewa Indra? The purpose of this study is to analyze, describe and add scientific insight about interpersonal communication and love contained in interpersonal communication between Yudistira and Dewa Indra, as well as to invite the public to re-understand the Mahabharata stories to be used as sesuluh in living this life.This research use desciptive qualitative approach. While this type of research is library research. Studying the Mahabharata story is because in the story there are very many types of communication, religious values, social relations, both between humans and God, between humans and humans and humans and nature. Based on the results of this study, it will be found that interpersonal communication and Yudistira's love are contained in the interpersonal communication between Yudistira and Dewa Indra in the Mahabharata Story